Pengaruh Pengangguran Terhadap Kemiskinan Di Sumatera Utara - Anisah Salsabila Nasution; Khairina Tambunan (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
Poverty is caused by various human needs, the existence of unequal patterns of thinking about resources that lead to an unequal distribution of income, it can be seen that the majority of the poor only have a limited amount of natural resources. In addition, the level of education also affects the quality of human resources. The purpose of this study was to determine the effect of unemployment on poverty in North Sumatra. This research method uses a quantitative strategy which is tested using SPSS 24 and the data obtained are taken from the Central Statistics Agency (BPS) in North Sumatra. The results of this study that the results of the normality test show a significance level greater than α (α = 0.05) that is 0.200 > 0.05, which means that the data is normally distributed.